Economic burden of hospitalizations of Medicare beneficiaries with heart failure - Kilgore M; Patel HK; Kielhorn A; Maya JF; Sharma P (Dove Medical Press, 2017)
Meredith Kilgore,1 Harshali K Patel,2 Adrian Kielhorn,2 Juan F Maya,2 Pradeep Sharma1 1Department of Health Care Organization and Policy, School of Public Health, University of Alabama at Birmingham, Birmingham, AL, 2Amgen, Inc., Thousand Oaks, CA, USA Objective: The objective of this study was to assess the costs associated with the hospitalization and the cumulative 30-, 60-, and 90-day readmission rates in a cohort of Medicare beneficiaries with heart failure (HF).Methods: This was a retrospective, observational study based on data from the national 5% sample of Medicare beneficiaries. Inpatient data were gathered for Medicare beneficiaries with at least one HF-related hospitalization between July 1, 2005, and December 31, 2011. The primary end point was the average per-patient cost of hospitalization for individuals with HF. Secondary end points included the cumulative rate of hospitalization, the average length of hospital stay, and the cumulative 30-, 60-, and 90-day readmission rates.Results: Data from 63,678 patients with a mean age of 81.8 years were included in the analysis. All costs were inflated to $2,015 based on the medical care component of the Consumer Price Index. The mean per-patient cost of an HF-related hospitalization was $14,631. The mean per-patient cost of a cardiovascular (CV)-related or all-cause hospitalization was $16,000 and $15,924, respectively. The cumulative rate of all-cause hospitalization was 218.8 admissions per 100 person-years, and the median length of stay for HF-related, CV-related, and all-cause hospitalizations was 5 days. Also, 22.3% of patients were readmitted within 30 days, 33.3% were readmitted within 60 days, and 40.2% were readmitted within 90 days.Conclusion: The costs associated with hospitalization for Medicare beneficiaries with HF are substantial and are compounded by a high rate of readmission. Keywords: heart failure, Medicare, health economics, hospitalization, costs